2017
DOI: 10.1016/j.meteno.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of orthologous cyanobacterial aldehyde deformylating oxygenases in the production of volatile C3-C7 alkanes in engineered E. coli

Abstract: Aldehyde deformylating oxygenase (ADO) is a unique enzyme found exclusively in photosynthetic cyanobacteria, which natively converts acyl aldehyde precursors into hydrocarbon products embedded in cellular lipid bilayers. This capacity has opened doors for potential biotechnological applications aiming at biological production of diesel-range alkanes and alkenes, which are compatible with the nonrenewable petroleum-derived end-products in current use. The development of production platforms, however, has been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…This might be due to the fact that ADO could produce both alkane and fatty alcohol, diverting the yield of alkane biosynthesis. Apart from production by ADO, the metabolic engineered cells containing aldehyde producing enzymes can also generate fatty alcohols from endogenous aldehyde reductases (Figure 1) [8,16,62]. Our studies demonstrated that yield of fatty alcohol products in whole cell biocatalysis can be affected by oxygen concentration.…”
Section: Discussionmentioning
confidence: 73%
“…This might be due to the fact that ADO could produce both alkane and fatty alcohol, diverting the yield of alkane biosynthesis. Apart from production by ADO, the metabolic engineered cells containing aldehyde producing enzymes can also generate fatty alcohols from endogenous aldehyde reductases (Figure 1) [8,16,62]. Our studies demonstrated that yield of fatty alcohol products in whole cell biocatalysis can be affected by oxygen concentration.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, bacterial ADs are small soluble proteins, which allows them to be studied in vitro more readily, leading to their wider use in metabolic engineering [11,15,[23][24][25][26]. Although new bacterial AD is constantly being characterized and engineered for alkane production [11,22,23,27,28], our experiments showed that protein accumulation of bacterial ADs is limited in vivo. It was also reported that there is no significant accumulation of most bacterial AD in E. coli during incubation [15], and even a decrease in AD abundance after 10 h of incubation [28].…”
Section: Introductionmentioning
confidence: 80%
“…Although new bacterial AD is constantly being characterized and engineered for alkane production [11,22,23,27,28], our experiments showed that protein accumulation of bacterial ADs is limited in vivo. It was also reported that there is no significant accumulation of most bacterial AD in E. coli during incubation [15], and even a decrease in AD abundance after 10 h of incubation [28]. The low levels of AD might be due to fast in vivo degradation, which can limit the application of AD for alkane biosynthesis.…”
Section: Introductionmentioning
confidence: 82%
“…Although new bacterial AD is constantly being characterized and engineered for alkane production [11,22,23,27,28], our experiments showed that protein accumulation of bacterial ADs is limited in vivo. It was also reported that there is no significant accumulation of most bacterial AD in E. coli during incubation [15], and even a decrease in AD abundance after 10 h of incubation [28]. The low levels of AD might be due to fast in vivo degradation, which can limit the application of AD for alkane biosynthesis.…”
Section: Introductionmentioning
confidence: 80%
“…ADs are small soluble proteins, which allows them to be studied in vitro more readily, leading to their wider use in metabolic engineering [11,15,[23][24][25][26]. Although new bacterial AD is constantly being characterized and engineered for alkane production [11,22,23,27,28], our experiments showed that protein accumulation of bacterial ADs is limited in vivo. It was also reported that there is no significant accumulation of most bacterial AD in E. coli during incubation [15], and even a decrease in AD abundance after 10 h of incubation [28].…”
Section: Introductionmentioning
confidence: 97%